Revisiting the Effect of Job Satisfaction and Organizational Culture on Employee Performance: The Mediating Role of Organizational Citizenship Behaviour - Setiani Setiani; Siswanto Siswanto; Siti Robithoh (Shirkah: Journal of Economics and Business, 2023)
Research on organizational citizenship behaviour is intriguing because it is often seen as an important asset to bring new perspectives and ideas to improve organizational performance and culture. However, the factors affecting OCB still need more empirical evidence. This study aimed to determine the effect of job satisfaction and organizational culture on employee performance with OCB as a moderating variable at P.T. Magnum Attack Indonesia. This study used a quantitative approach with a questionnaire survey of 89 respondents. The data analysis method uses SEM-PLS. The results showed that job satisfaction had no significant effect on employee performance and OCB. Organizational culture does not affect employee performance but shows a significant effect on OCB. OCB did not mediate the relationship between job satisfaction and employee performance, as well as organizational culture and employee performance. The research suggests that P.T. Magnum Attack Indonesia should enhance the Organizational Citizenship Behaviour (OCB) of individual employees by fostering a culture of care for colleagues, discipline in work, mutual respect, and assistance among co-workers. Consistently practicing OCB can lead to the development of a positive organizational culture.